Soft Power for Aceh Conflict Resolution and Political Decentralization - Gladis Herazati; Rahyunika Azzahra; Fransisca Yesianti; Ayu Andini; Hayyu Angreni; Wanda Kurnia; Paskaria Erni Kurniati; Dira Adetya Frisca; Winda Sartika Sari; Jagad Aditya Dewantara (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
From various kinds of history originating from Aceh, the tragedy is quite a lot colored by violence. Starting from the Soekarno era to the Megawati era. From each era of government, the handling that was carried out also varied greatly. The dialogue approach began during the Abdurrahman Wahid Administration. There was an agreement between the Government of Indonesia and the Free Aceh Movement (GAM) that it would stop the violence mediated by HDC. The agreement was the Joint Understanding on Humanitarian Pause for Aceh (Humanitarian Pause Agreement) on May 12, 2000, but the Acehnese people ignored this agreement where the security situation in Aceh was still colored by violence. When the Government of Indonesia changed its leader to become Megawati, acts of violence continued to occur in Aceh and efforts were made again by HDC with the signing of the Cessation of Hostilities Agreement on December 12, 2022. However, this was still not able to reduce the acts of violence that occurred. . On May 19, 2003 Aceh was declared under military emergency status. It was only during the reigns of Susilo Bambang Yudhoyono and Jusuf Kalla that the Aceh conflict was resolved peacefully as evidenced by the signing of a Memorandum of Understanding in Helsinki on 15 August 2005, which brought Aceh from war to peace.